Acute Disseminated Encephalomyelitis Associated with Cytomegalovirus Infection in an Immunocompetent Subject - Shen, Hsiu-Chu; Lin, Chien-Jen; Lin, Huey-Juan (Journal of Neurology and Epidemiology, 2014)
Purpose: Fulminant acute disseminated encephalomyelitis (ADEM) associated with cytomegalovirus (CMV) infection in immunocompetent hosts is rare, and the MRI findings might be atypical. Case report: A 17-year-old immunocompetent man presented with acute flaccid paraplegia accompanied by bladder and bowel incontinence. The serum virology tests revealed the presence of CMV IgM and IgG, indicating reactivation of latent infection. MRI studies of the brain and the whole spinal cord showed diffuse gray matter lesions of hyperintense signals in T2. After aggressive rescue therapy combining intravenous immunoglobulin, pulse methylprednisolone and plasma exchange, the patient made a complete neurological recovery 6 months later. Conclusion: This report demonstrates the association of CMV infection with ADEM in an immunocompetent subject. Although the treatment regimen and timing for patients with ADEM need further investigation, aggressive rescue therapy by adopting multiple immunomodulatory treatments may be warranted.